(untitled) (Semiárida, 2020)
The vegetation is one the most important indicators of changes in ecosystems. Often this information is useful for determining homogeneous landscapes, essential when planning a sustainable system. The aim of this study was to perform a subdivision of landscapes in the Flooding Pampa by analyzing functional aspects of vegetation obtained by means of remote sensing. We used a series of 11 year normalized difference vegetation index (NDVI) obtained from the sensor TERRA/MODIS. These data were fitted to a mathematical model in TIMESAT, which enabled the extraction of seasonal growing season variables in states “El Niño”, Neutral and “La Niña” (periods 2002-2003, 2004-2005 and 2008-2009, respectively). Subsequently, we performed a Principal Component Analysis which showed a 85.65% variance explained in the first three components, enabling the distinction of four different landscapes with phenological behaviors. The Tall-tussock grass range and agricultural landscape has the largest values of productivity and high growth seasons, the agricultural and range “flechillar” is characterized by low maximum values of NDVI and high levels of productivity. The landscapes Southern agricultural and ecotone agricultural and range have a similar behavior with short growing seasons, high maximum values of NDVI and low productivity, but in the Southern agricultural landscape the growing season is premature.